Entrepreneurial Skills, Significant Differences between Serbian and German Entrepreneurs - Morales, Carlos E. (2013)
An extensive literature review reveals various authors acknowledge skills have an impact on entrepreneurial success. However, a lack of consensus regarding the main skills an entrepreneur needs is apparent. In this study, a contribution is made to the debate with empirical data and analysis, in two steps: by testing mean differences and reducing data with a principal components analysis. A sample of 394 potential entrepreneurs was administered the SAT-ECENT questionnaire, testing four skills: readiness to change, learning capacity, impact on people, and stress tolerance. The questionnaires were administered in Serbia (n = 190) and in Germany (n = 204). In this paper, evidence about two main issues is presented: Entrepreneurial skills vary significantly across countries, and the skill tolerance to stress plays an important role in explaining the variance in the development of entrepreneurial skills in the two countries. Discussion is focused on the research implications and relevance of the findings as well as the practical implications for entrepreneurship promotion programs.